Occupational health and safety management in the context of an ageing workforce. (July 2019) - Varianou-Mikellidou, Cleo; Boustras, Georgios; Dimopoulos, Christos; Wybo, Jean-Luc; Guldenmund, Frank W.; Nicolaidou, Olga; Anyfantis, Ioannis
Highlights: This paper is identifying age-related changes and their impacts on occupational health and safety. Work ability index is a tool proposed to measure a person's ability and performance. New emerging risks must be considered in the development of an OHSMS. Gaps in the field have been identified and a new research work is proposed. Abstract: During the last decades, humanity experiences an increasing demographic change. The relative percentage of older people is growing, while fewer young employees are entering the labour force. This phenomenon is directly connected with ageing of the workforce. Older workers constitute a special group with characteristics that require special attention from the Occupational Health and Safety (OHS) point of view. The aim of this paper is to address what changes occur in ageing workers as a result of physical and psychological processes and the possible impacts of these at work in relation to OHS and the concept of sustainable work and workplaces. In addition, this paper discusses factors affecting work ability and worker's performance in relation to the ageing phenomenon. Finally, based on the literature, the paper proposes measures to minimize age-related risks and increase awareness. These measures should be designed and adopted at the early stages of working life and continue until retirement. By reducing risk factors of employees, the rate of occupational accidents and occupational diseases may be decreased, thus saving costs for employers, health system and insurance costs, while simultaneously facilitating a healthier retirement for the working-age population.